RISK FACTORS OF CORONARY ARTERY STENOSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS - E. V. Gerasimova; T. V. Popkova; D. S. Novikova; L. B. Kruglyi; O. A. Fomicheva; Yu. A. Karpov; E. L. Nasonov (Научно-практическая ревматология, 2018)
Objective: to determine frequency and grade of the coronary artery (CA) damage using coronary angiography data in patients with rheumatoid arthritis (RA) and suspected coronary artery disease (CAD); to evaluate the association of its progress with traditional risk factors (TRF), inflammatory markers and antirheumatic therapy. Subjects and methods. 25 male and 38 female RA patients with suspected or verified CAD, (median age was 58 [52; 63] years, RA duration – 10,5 [7; 23] years), were included in the study. 85% of patients were seropositive for IgM rheumatoid factor, 69% – for cyclic citrullinated peptide (CCP) antibodies. DAS28 median was 4,7 [3,3; 5,8]. CA stenosis was diagnosed if hemodynamically significant narrowing of the artery lumen (≥50%) was present. Results and discussion. CA stenosis was diagnosed in 22 (35%) patients (group I), 15 (68%) of them had single vessel damage, 7 (32%) – three-vessel involvement; the damage of two vessels was not diagnosed in any RA case. 41 (65%) patients had no lesions in CA (group II). The frequency of CA stenosis was higher in male patients (15 out of 25; 60%) than in female (7 out of 38; 18%; p<0,05). CAD incidence in group I was higher than in group II: myocardial infarction (MI) history was documented in 32% and 2%, stable angina pectoris in 77% and 32% of cases respectively, p><0,05. TRF incidence was similar in both groups. Concentration of serum high density lipoprotein cholesterol (HDLC) in group I was lower than in group II (median 1,2 [1,0; 1,5] vs 1,3 [1,2;1,8] mmol/L respectively, p=0,025). Carotid artery atherosclerotic plaques were detected in 19% and 16%, carotid artery intimamedia thickening – in 53% and 57% of patients respectively (p>0,05). The multiple regression analysis did not revealed any direct relationship of CA stenosis development with age, gender, DAS28, erythrocyte sedimentation rate, C-reactive protein level, concentration of cholesterol, low density lipoprotein cholesterol, HDLC, and consumption of anti-rheumatic drugs. The prediction of CA stenosis development was not possible with parameters used in this study. However, differences in age were the closest to statistical significance (OR=0,85; 95% CI [0,72–1,0], p=0,05). Other parameters, including HDLC level< 1,2 mmol/L for women and< 1,0 for men (OR 0,82; 95% CI [0,64–0,90], p=0,09) had less predictive power. Conclusion: CA stenosis was diagnosed in every third patient with RA and suspected CAD or verified CAD. Male gender and low level of HDLC may increase the risk of CA stenosis.